2005
DOI: 10.1063/1.1871913
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the density-functional based tight-binding approximation method for the calculation of reaction energies and other data

Abstract: We investigated the performance of the approximative density functional method DFTB versus BLYP and G2 with respect to zero-point corrected reaction energies, vibrational frequencies, and geometry parameters for a set of 28 reactions and 22 representative molecules containing C, H, N, and O (DFTB--density-functional based tight-binding approximation). The DFTB reaction energies show a mean absolute deviation versus the G2 reference of 4.3 kcalmol only. The corresponding value for the vibrational frequencies am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
168
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 148 publications
(178 citation statements)
references
References 19 publications
8
168
0
2
Order By: Relevance
“…The applicability of SCC-DFTB method to molecular systems has been tested by several independent benchmark studies [90][91][92], which found that it gives, in general, similar energetics as other NDDO methods, but somewhat better geometries and vibrational frequencies. To determine whether an approximate (QM) method provides a meaningful description for a particular problem, however, it is important to carry out additional benchmark calculations most relevant to the system or problem in hand.…”
Section: Qm/mm Analysis Of Proton Transfersmentioning
confidence: 97%
“…The applicability of SCC-DFTB method to molecular systems has been tested by several independent benchmark studies [90][91][92], which found that it gives, in general, similar energetics as other NDDO methods, but somewhat better geometries and vibrational frequencies. To determine whether an approximate (QM) method provides a meaningful description for a particular problem, however, it is important to carry out additional benchmark calculations most relevant to the system or problem in hand.…”
Section: Qm/mm Analysis Of Proton Transfersmentioning
confidence: 97%
“…However, multiple interlayer bonding formed over sizeable vacancy sites has a high probability to remain as a localized amorphous domain of several carbon atoms kinetically jammed near the existing defects. To further support this conjecture, we performed growth simulations using self-consistent charge density functional tight binding molecular dynamics 33 , which allows quantum calculations of DFT accuracy in realistic simulations involving a large number of carbon atoms 34 . As fullerene molecules thermally decompose, various carbon structures of different molecular weight are available near the template graphene.…”
Section: Discussionmentioning
confidence: 99%
“…DFTB2 has been particulariy parametrized for O, N, C, H [9], S [43] and Mg [44], a parameter set called mio. These ONCH parameters have been tested quite intensely with respect to their performance for atomization and reaction energies, molecular geometries, vibrational frequencies, ionization potentials and electron affinities, dipole moments and for non-covalent interactions [45][46][47]. DFTB2 performs very well for reaction energies [45], while for heats of formation other SE methods, in particular the newly developed OMx and PDDG-PM3 methods, turned out to be slightly superior.…”
Section: Performance and Testsmentioning
confidence: 99%